Kinerja Struktur Gedung Beraturan Dual System (Concrete Frame - RC Wall Structures) Menggunakan Metode Direct Displacement Based Design Dan Capacity Spectrum Method - Purba, Raja Parulian; Djauhari, Zulfikar; Suryanita, Reni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Earthquake resistant structural design commonly used the concept of forced-based design (FBD). The concept is only based on the analysis of elastic structures and not directly indicated the performance of the building against the effects of the occurred earthquake. So, it requires a performance evaluation by conducting analyzes to reach a state of inelastic structure called the concept of performance-based design (PBD). In this study, there are two methods of performance analysis that were based on the lateral displacement of the inelastic conditions, the methods are Direct Displacement Based Design (DDBD) and Capacity Spectrum Method (CSM). The purposes of this study are to identify and to compare between the performance parameters of the methods. The structural model is a dual system regular building which combine a frame structure and reinforced concrete wall. The seismic load design in this study based on SNI 1726-2012. The reviewed parameter values are the displacement, base shear force, effective damping, and effective vibrating times. The results of this study indicated that all the parameter values of the DDBD method analysis are larger than CSM method. DDBD method produced a target displacement 0.545 m, the base shear force 38293.25 kN, effective damping 14.01%, and the effective vibrating times 3.826 seconds. Mean while the method of CSM produced target displacement 0.175 m, the base shear force 21728.978 kN, effective damping 5.40% and the effective vibrating times of 1.314 seconds. The evaluation of the structure performances which is based on ATC-40 indicated the DDBD method was on damage control level, whereas the CSM method was on the immediate occupancy level.Keywords: Inelastic, dual system regular building structure, direct displacement based design, capacity spectrum method, structure performance.